Sintesis dan Karakterisasi Silika Berpori dari Natrium Silikat dan Gelatin dari Kulit Ikan Lele Clarias gariepinus sebagai Surfaktan - Zahran, Jihan Fadhilah; Aini, Syamsi; Riga, Riga; Suryani, Okta (Departemen Kimia FMIPA UNP, 2024)
Previous research result on porous silics have obtained fine silica precipitate with a purity of 70,6% and a partticle size of 300-1000 nm. As the application of porous silica increases, research is also developing, one example is mesoporous silica. Mesoporous silica can be used in various fields such as catalysts, drug delivery, adsorption, chromatography and others. This research was conducted to synthesize silica with catfish skin gelatin surfactant. Gelatin was characterized by FTIR to see the functional groups that make up gelatin. The resulting silica was characterized using XRD to determine the crystal structure and SEM to determine the morphology of the silica. The results of the FTIR test on catfish skin gelatin showed 4 absorption areas, namely Amide A, Amide I, Amide II and Amide III. Silica characterization using XRD shows crystalline crystals. Meanwhile, SEM characterization shows regular morphology. SL4% has the highest crystallinity and branched tube shape morphology.